The Right to Remain “Silent": Deaf Aesthetics in GANGSTA - Pang, Aidan (Performance Matters, 2022)
In the opening to every episode in the Japanese anime series GANGSTA., the following notice appears: “Due to the nature of the main character, subtitles will appear in some places.” Such a narrative choice challenges what it means to hear, revealing how deafness offers more in the way of hearing than its normative definition suggests. GANGSTA.’s portrayal of how the deaf hitman Nicolas Brown uses sound to challenge ableist conceptions of deafness shifts the voyeuristic ear on disability from the so-called disabled body to the able-bodied. To hear sound is a political act, such that it is necessary to ask who has a claim to this sensory experience. What currently qualifies as listening is based on an ableist listening experience, and while the deaf and hard of hearing may utilize other modes of listening, it does not mean they have no say in the realm of sound. Thus, I examine how the aural aesthetics of deafness can be used to disrupt and restructure an ableist politics of listening through the ear.